Toward Civic Co-production: Using Worldbuilding to Go Beyond Participation in Urban Planning and Enact More Equitable Cities - Hoffman, Johanna (Frontiers in Sustainable Cities, 2022)
Even as calls for more participatory urban planning have grown over the past half century, achieving meaningful and effective participation remains elusive. While disciplines beyond urban development are experimenting with narrative-driven engagement toolsets to cultivate greater degrees of public investment and collaborative capacity, less exploration on the power of such tools has been conducted in urban development circles. Towards the objective of reconciling the challenges of community engagement with the growing uncertainties and inequalities of contemporary cities, this paper explores the value of aiming beyond participatory planning towards co-production, and assesses the role of worldbuilding, a design approach with origins in fiction, in doing so. Specifically, the worldbuilding methods implemented in a project to envision dense urban environments in 2070 is positioned within growing calls for urban development to move towards co-production. The paper contributes to the wider discourse on tactics for collaboratively envisioning and enacting more equitable cities.